Changing pattern of recurrences in patients with early HER2-positive breast cancer receiving neoadjuvant chemotherapy in the era of dual anti-HER2 therapy. Issue 1121 (19th April 2019) - Chiu, Joanne W; Leung, Roland; Tang, Vikki; Cheuk, Wai Yin; Lo, Jessica; Kwok, Gin Wai; Wong, Hilda; Suen, Dacita; Cheung, Polly; Wong, Ting Ting; Yau, Thomas; Kwong, Ava
Abstract: Background: Over the last 10 years, there has been a major treatment revolution for early human epidermal growth factor receptor 2 (HER2)–positive breast cancer. We aimed to explore the outcome of different neoadjuvant chemotherapy in a tertiary breast cancer centre with early HER2-positive breast cancer as well as factors associated with pathological complete response (pCR) and recurrence-free survival (RFS). The pattern of recurrence was also studied. Methods: This retrospective study analysed the outcome of neoadjuvant chemotherapy during the period 2005 to 2016 in a tertiary referral centre in Hong Kong. Patients were divided into three groups according to the neoadjuvant chemotherapy they received: chemotherapy only (Chemo), chemotherapy plus trastuzumab (Chemo-H) and chemotherapy plus double anti-HER2 therapy (Chemo-DH). Results: There were 226 cases analysed during the study period. The rate of pCR was 5%, 26% and 60% in Chemo, Chemo-H and Chemo-DH groups, respectively (Chemo vs pooled Chemo-H/DH: p<0.0001; Chemo-H vs Chemo-DH: p<0.0001). This was accompanied by a trend of increased rate of breast conservation therapy in Chemo-DH cohort (p=0.046). Use of double anti-HER2 therapy, older age (>50 years) and hormone receptor negativity were associated with more pCR. pCR was associated with better RFS. Among those with recurrence, the proportion of patients with brain as the only site of recurrence increased remarkably with more efficacious anti-HER2 treatment (0% in Chemo, 8% in Chemo-H, 67% in Chemo-DH). Conclusion: pCR remains an important predictive factor for improved RFS. In the era of dual anti-HER2 neoadjuvant therapy, brain-only recurrence poses a challenge to disease surveillance and treatment.